Observational Constraints on Primordial Black Hole Dark Matter - Gorton, Matthew (2025)
In spite of compelling evidence for its existence and great experimental efforts to detect it, the nature of dark matter remains unknown. One scenario is that some or all of the dark matter consists of black holes formed from the collapse of highly overdense regions in the early Universe. Observational constraints on these `primordial black holes' (PBHs) appear to exclude PBHs from making up all of the dark matter unless their mass, MPBH, lies in the range 1017 g ≲ MPBH ≲ 1022 g, often known as the `asteroid-mass window'. In this thesis we investigate the impact of assumptions made when calculating observational constraints on PBHs.